Implications of the Electrodeposition Scan Rate on the Morphology of Polyaniline Layer and the Impedance of a QCM Sensor - Putri, Nugrahani Primary; Suaebah, Evi; Rohmawati, Lydia; Santjojo, Dionysius Joseph Djoko Herry; Masruroh, Masruroh; Sakti, Setyawan Purnomo (Trends in Sciences, 2023)
This work aims to determine how the scan rate affects PANI layers' morphology and resonance parameters deposited on quartz crystal microbalance (QCM). The PANI layer was produced using the electrodeposition method with a scan rate variation of 10 to 50 mV/s. The PANI layer deposited at a scan rate of 10 mV/s has an aggregate morphology, whereas the morphology becomes more scattered at a higher scan rate. On the other hand, the homogeneity of the distribution of PANI particles increases due to the increase in the scan rate. The QCM impedance profile also changes with PANI layer deposition at different scan rates. The QCM impedance profile with the PANI layer that is most similar to the uncoated QCM impedance profile is at a scan rate of 10, 40 and 50 mV/s. The resonance parameters, which represent the inertial mass and the dissipative characteristics of the PANI layer, were investigated. The PANI layer with the smallest resonance parameter has a scan rate of 10 and 40 mV/s. Therefore, the 2 scan rates are the best candidates to be applied further. HIGHLIGHTS The electrodeposition scan rate influences the morphology of the PANI layer deposited above QCM The amount of carbon distributed across the QCM surface represents how effective the PANI deposition was The resulting morphology will impact the PANI layer's impedance characteristic and resonance parameter values GRAPHICAL ABSTRACT